Testing of Remotely Controlled Soil Moisture Sensors and Analysis of Soil Moisture Data - Montes Cañizares, Roberto (My University, 2010)
A theoretical study and analysis of soil moisture data at Remningstorp area from spring 2006 to winter 2009 has been performed. Water volume content has been compared with the precipitation in the area, as well as the ground temperature has been compared with the air temperature in the same area. One sensor was located in an open field and the second sensor was located inside the forest. Installation and testing of remotely controlled soil moisture sensor at Mölnlycke has also been completed in this master thesis work. An analysis of the water volume content data has been done to try to identify rainfall. The output data from the soil moisture measurement given by Aquaflex sensors consisted of three variables, which are related primarily to the real and imaginary components of the dielectric permittivity and temperature of the ground in degrees. The field sensor is surrounded by clay soils or clay-rich loams. This compacted soil absorbs and store moisture and retains water. The forest sensor is surrounded by silt, sand or sandy-loams. The ground in the open field is more easily heated, there is no vegetation or tree canopy and therefore the sun rays can easily heat the area. For those reasons the field sensor shows a stronger variation in its water volume content. The aquaflex sensor uses a direct method to measure the volumetric water content in the ground as well as the temperature. The results were accurate measurement of the water volume content and the temperature on the ground. The new remotely controlled soil moisture sensor allowed a fast and easy data access; however some problems were experienced with Aquaflex software installation in Windows Vista.
Keywords: Övrig annan teknik; Other Engineering and Technologies not elsewhere specified